Permanent pacemaker implantation in unexplained syncope patients with electrophysiology study-proven atrioventricular node disease. (24th May 2021) - Doundoulakis, I; Gatzoulis, KA; Arsenos, P; Dilaveris, P; Tsiachris, D; Antoniou, CK; Sideris, S; Kordalis, A; Soulaidopoulos, S; Laina, A; Tsioufis, K
Abstract: Funding Acknowledgements: Type of funding sources: None. Background/Introduction: Syncope, whose cause is unknown after an initial assessment, has an uncertain prognosis. It is critical to identify patients at highest risk who may require a pacemaker and to identify the cause of recurrent syncope to prescribe proper therapy Purpose: Aim of this study was to evaluate the effect of permanent pacing on the incidence of syncope in patients with unexplained syncope and electrophysiology study-proven atrioventricular node disease. Methods: This was an observational study based on a prospective registry of 236 consecutive patients (60.20 ± 18.66 years, 63.1% male, 60.04 ± 9.50 bpm) presenting with recurrent unexplained syncope attacks admitted to our hospital for invasive electrophysiology study (EPS). Τhe implantation of a permanent antibradycardia pacemaker (ABP) was offered to all patients according to the results of the EPS. 135 patients received the ABP, while 101 denied. Results: The mean of reported syncope episodes was 1.97 ± 1.10 (or presyncope 2.17 ± 1.50) before they were referred for a combined EP guided diagnostic and therapeutic approach. Over a mean follow-up of approximately 4 years (49.19 ± 29.58 months), the primary outcome event (syncope) occurred in 31 of 236 patients (13.1%), 6 of 135 (4.4%) in the ABP group as compared to 25 of 101 (24.8%) in the no pacemaker group (p < 0.001). Conclusion: Among patients with a history of unexplained syncope, a set of positivity criteria for the presence of EPS defined atrioventricular node disease, identifies a subset of patients who will benefit from permanent pacing.